Genetic similarity of Jatropha curcas accessions based on AFLP markers - Santos,Carlos Antonio Fernandes (2010)
The genetic relationships between accessions of Jatropha (Jatropha curcas) were determined based on AFLP marker. A set of 50 plants from 12 accessions of J. curcas was analyzed with molecular data from 164 loci generated from 17 AFLP primer combinations. Molecular variance of data was analyzed by total decomposition between and within accessions. An UPGMA dendrogram was constructed based on genetic distances estimated by Jaccard's similarity coefficient. The well-defined dendrogram showed a cophenetic value of 0.91. Groups of plants were observed in six of the 12 accessions studied with similarity of over 30 %, indicating high genetic variability. The variation among accessions was estimated to be 0.275, also indicating high variability. These results show that the genetic variability of the studied J. curcas accessions is structured according to the origin and that a greater number of populations should be sampled to increase the genetic diversity of the studied genebank.